2010
DOI: 10.1007/s12393-010-9015-3
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Pulsed Electric Field Treatments for the Enhancement of Mass Transfer from Vegetable Tissue

Abstract: In the last decades, several non-thermal technologies have been proposed as alternative to the traditional ones to improve the competitiveness of the food industry. The key to success was identified in offering to food industries the opportunity to improve food quality, to introduce new foods in the market, and to optimize the processing procedures while reducing energy costs. Pulsed electric fields (PEF) showed the potential to be one of the most promising novel technologies to reach these objectives.\ud The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 291 publications
(148 citation statements)
references
References 118 publications
(247 reference statements)
2
132
0
7
Order By: Relevance
“…It has previously been reported that PEF treatment also improves the antioxidant activity of the wine obtained after pressing PEF pre-treated grapes by 20 % (Donsi et al 2010a). In addition, an investigation of apple juice extracts obtained after pressing PEF pre-treated cut or whole apples revealed an increase in antioxidant activity in the range 30-50 % compared to the control extraction (Grimi et al 2011).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…It has previously been reported that PEF treatment also improves the antioxidant activity of the wine obtained after pressing PEF pre-treated grapes by 20 % (Donsi et al 2010a). In addition, an investigation of apple juice extracts obtained after pressing PEF pre-treated cut or whole apples revealed an increase in antioxidant activity in the range 30-50 % compared to the control extraction (Grimi et al 2011).…”
Section: Resultsmentioning
confidence: 89%
“…According to Jaeger et al (2012), high intensity treatment may cause softening of the plant tissues to an extent that is unfavourable for de-juicing i.e., causes the compaction and closing of the capillaries in the press cake. The application of PEF in combination with mechanical juice expression by pressing was demonstrated to be effective for improving juice yield from different plant-based materials (Donsi et al 2010a). The reported improvement of the juice yields varies widely, most likely due to different intrinsic characteristics of the tissues and process conditions employed in different studies (degree of particles fragmentation, PEF parameters and compression pressure) (Jaeger et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations